Designing Big Story Book Project (BSBP) in Teaching Reading Comprehension - Aswin Abbas (Universitas Cokroaminoto Palopo, 2017)
This research aimed find out the effectiveness of using big story book project (BSBP) in teaching reading comprehension and to know the advantages and the disadvantages of using BSBP in teaching reading comprehension. The researcher applied pre-experimental research design and consists of pre-test, treatment and post-test in order to find whether the big story book project (BSBP) effective in teaching reading comprehension. The instruments used in this research were reading test and questionnaire. The result from this research shows that using big story book project (BSBP) in teaching reading comprehension is effective. It is proved by the result that there is significant difference between the result of the students’ mean score in the pre-test and the post-test. In the pre-test, the students’ mean score is (43.79) and in the post-test is (80.37). Furthermore, it is proved by the probability value is smaller than α (0.00 < 0.05). On the other word, BSBP has advantages to the students if applied in teaching and learning process, especially in reading subject.